STAT3/Mitophagy Axis Coordinates Macrophage NLRP3 Inflammasome Activation and Inflammatory Bone Loss. (30th December 2022) - Zhu, Lingxin; Wang, Zijun; Sun, Xiaoyue; Yu, Jingjing; Li, Ting; Zhao, Huan; Ji, Yaoting; Peng, Bin; Du, Minquan
ABSTRACT: Signal transducer and activator of transcription 3 (STAT3), a cytokine‐responsive transcription factor, is known to play a role in immunity and bone remodeling. However, whether and how STAT3 impacts macrophage NLR family pyrin domain containing 3 (NLRP3) inflammasome activation associated with inflammatory bone loss remains unknown. Here, STAT3 signaling is hyperactivated in macrophages in the context of both non‐sterile and sterile inflammatory osteolysis, and this was highly correlated with the cleaved interleukin‐1β (IL‐1β) expression pattern. Strikingly, pharmacological inhibition of STAT3 markedly blocks macrophage NLRP3 inflammasome activation in vitro, thereby relieving inflammatory macrophage‐amplified osteoclast formation and bone‐resorptive activity. Mechanistically, STAT3 inhibition in macrophages triggers PTEN‐induced kinase 1 (PINK1)‐dependent mitophagy that eliminates dysfunctional mitochondria, reverses mitochondrial membrane potential collapse, and inhibits mitochondrial reactive oxygen species release, thus inactivating the NLRP3 inflammasome. In vivo, STAT3 inhibition effectively protects mice from both infection‐induced periapical lesions and aseptic titanium particle‐mediated calvarial bone erosion with potent induction of PINK1 and downregulation of inflammasome activation, macrophage infiltration, and osteoclast formation. This study reveals the regulatory role of the STAT3/mitophagy axis at the osteo‐immune interface and highlights a potential therapeutic intervention to prevent inflammatory bone loss. © 2022 American Society for Bone and Mineral Research (ASBMR). Abstract : Schematic illustration. In both non‐sterile and sterile inflammatory osteolysis, macrophage hyperactivated STAT3 is highly correlated with the cleaved IL‐1β expression. Targeting STAT3 using stattic blocks macrophage NLRP3 inflammasome activation through triggering PINK1‐dependent mitophagy that eliminates dysfunctional mitochondria, thereby relieving inflammatory macrophage‐amplified osteoclast formation in vitro and protecting mouse inflammatory osteolysis in vivo.